PENGARUH PROJECT BASED LEARNING BERBANTUAN MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X PADA MATERI PERUBAHAN LINGKUNGAN - Yuli Munda Yana; Irwan Hanafi; Ratih Komala Dewi; Darmanella Dian Eka Wati; Afrahamiryano; Helvita Roza; Chairul Amri (Universitas Cokroaminoto Palopo, 2026)
The low ability of students' creative thinking skills is still a major problem in learning biology, especially in environmental change materials that require analytical and problem-solving skills. This study aims to analyze the effect of the application of the Project Based Learning (PjBL) model assisted by Mind Mapping on the creative thinking ability of class X students of SMAN 4 Solok City. This study uses a quantitative approach with a quasi-experimental method and a post-test only control group design. The research sample consisted of 41 students who were divided into an experimental class (22 students) and a control class (19 students). The research instrument is in the form of a test of creative thinking ability which includes indicators of fluency, flexibility, originality, and elaboration. Data were analyzed using the Liliefors normality test, homogeneity test, and Welch t-test at a significance level of 0.05. The results showed that there was a significant difference between the creative thinking skills of students in the experimental class and the control class, with the value of t calculated (2.32) greater than the t value of the table (2.02). The average post-test score of the experimental class (78.6) was higher than that of the control class (66.7). Thus, it can be concluded that the application of the PjBL model assisted by Mind